Comprehensive Analysis of Adverse Events Associated With Per Oral Endoscopic Myotomy in 1826 Patients: An International Multicenter Study. (August 2017) - Haito‐Chavez, Yamile; Inoue, Haruhiro; Beard, Kristin W; Draganov, Peter V; Ujiki, Michael; Rahden, Burkhard H A; Desai, Pankaj N; Pioche, Mathieu; Hayee, Bu; Haji, Amyn; Saxena, Payal; Reavis, Kevin; et al.
Abstract : Objectives: The safety of peroral endoscopic myotomy (POEM) is still debated since comprehensive analysis of adverse events (AEs) associated with the procedure in large multicenter cohort studies has not been performed. To study (1) the prevalence of AEs and (2) factors associated with occurrence of AEs in patients undergoing POEM. Methods: Patients who underwent POEM at 12 tertiary‐care centers between 2009 and 2015 were included in this case–control study. Cases were defined by the occurrence of any AE related to the POEM procedure. Control patients were selected for each AE case by matching for age, gender, and disease classification (achalasia type I and II vs. type III/spastic esophageal disorders). Results: A total of 1, 826 patients underwent POEM. Overall, 156 AEs occurred in 137 patients (7.5%). A total of 51 (2.8%) inadvertent mucosotomies occurred. Mild, moderate, and severe AEs had a frequency of 116 (6.4%), 31 (1.7%), and 9 (0.5%), respectively. Multivariate analysis demonstrated that sigmoid‐type esophagus (odds ratio (OR) 2.28, P =0.05), endoscopist experience <20 cases (OR 1.98, P =0.04), use of a triangular tip knife (OR 3.22, P =0.05), and use of an electrosurgical current different than spray coagulation (OR 3.09, P =0.02) were significantly associated with the occurrence of AEs. Conclusions: This large study comprehensively assessed the safety of POEM and highly suggests POEM as a relatively safe procedure when performed by experts at tertiary centers with an overall 7.5% prevalence of AEs. Severe AEs are rare. Sigmoid‐type esophagus, endoscopist experience, type of knife, and current used can be considered as predictive factors of AE occurrence.